Prevalence of awake Bruxism: A systematic review - Oliveira, Júlia Meller Dias de; Pauletto, Patrícia; Massignan, Carla; D'Souza, Neena; Gonçalves, Daniela Aparecida de Godoi [UNESP]; Flores-Mir, Carlos; De Luca Canto, Graziela (Elsevier, 2023)
Objectives: To identify the prevalence of Awake Bruxism (AB). Sources: The electronic search was done in Embase, PubMed/MEDLINE, LILACS, Livivo, Scopus, and Web of Science databases up to January 2nd, 2023. The search strategies combined terms such as bruxism, awake, and related terms when conducting searches in databases. Grey literature was consulted through Google Scholar, ProQuest, and OpenGrey. Study selection: Two independent reviewers participated in the study selection stages and included observational studies assessing the prevalence of AB, detected using reporting feedback (self or family report), clinical examination, and/or instrumental methods, regardless of the sex and age of the population. Data: Methodological quality was assessed using the Joanna Briggs Institute's checklist for prevalence studies. Ratio meta-analyses were performed using R Statistics software. Results: From a total of 3,083 studies identified by the searches on databases, 322 articles were reviewed the full-text and a total of 81 (quantitative synthesis) and 83 (narrative synthesis) studies were included. Only fifteen studies reached complete methodological quality. Two overall meta-analyses were performed, grouped based on convenience and population-based samples. The overall prevalence for possible AB was 32.08 % and 16.16 %, respectively. For the subgroup analyses, the prevalence rate showed a wide variation in different studied populations, approximately 14 %–32 % for women and 19 %–30 % for men, for population-based and convenience studies, respectively. Conclusion: Possible AB prevalence was set from 16 % to 32 %. Studies with probable AB and definitive AB are still necessary. Clinical Significance: Studying the prevalence of waking bruxism is of interest to both dentists and patients. Knowing the probability of patients having awake bruxism allows the dentist to offer comprehensive preventive approaches to patients, avoiding deleterious consequences resulting from this condition. The present study reveals that the condition of bruxism during wakefulness is present in one out of every six adult patients studied. In pediatric patients, although this condition seems to be equally present, not enough studies were found to support this information for probable and definitive bruxism.
Keywords: Awake bruxism; Bruxism; Evidence-based dentistry; Prevalence; Systematic review